Integritas Intelectual, Emotional, And Spiritual Quotient Dalam Pembentukan Nafsul Muthmāinnah Untuk Mewujudkan Komunikasi Qur`Ani - Roiyani; Kusmawati Hatta (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This study aims to find out how the Rule Model of Quranic Communication Psychology is a process of the integrity of IESQ Qur'ani intelligence in the formation of Nafsul-Muthmāinnah towards someone so that Islamic communication is realized. This study uses a qualitative method approach, with discourse analysis techniques and text interpretation. This method analyzes the process of a meaning contained behind the information contained in the Koran. The verses that explain the existence of IESQ in Nafs are found in QS. Yusuf/12:53, QS. Al-Qiyamah/75:2, QS. Al-Fajr:27-28, QS. ar-Ra’d/13:28, QS. al-Jatsiyah/45:5 dan HR.Muslim. while the verses explaining the integration of the IESQ through the Quranic Communication Psychology process are contained in QS. an-Nisa/4:9, QS. al-Ahzab/33:32, QS. an-Nisa/4:63, QS. al-Isra’/17:23, QS. Thaha/20:43-44 dan QS. al-Isra’/17:28. The results of the analysis of these verses are that Nafs is a container for sharing information and knowledge that has the characteristics of Resentment, Despicable and Peaceful. 'Aqal is the potential of the soul that has the ability to process information so that it becomes knowledge. While the process of delivering messages or information by applying the principles of Quranic Communication Psychology.